IMPLEMENTATION OF INDEPENDENT STUDY TECHNIQUES IN TEACHING EFL - Gulbegim Jo‘rayeva; Kamalova Sitora (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article explores the implementation of independent study techniques in teaching English as a Foreign Language (EFL). Independent study, as an approach to language learning, promotes learner autonomy and self-directed learning. The study aims to examine the benefits of incorporating independent study techniques in EFL classrooms, discuss effective strategies for implementing independent study, and highlight the impact on students' language proficiency. The research draws on a comprehensive review of relevant literature and empirical studies in the field of EFL education. The findings indicate that independent study techniques provide opportunities for students to take control of their learning, enhance their language skills, and foster lifelong learning habits. This article emphasizes the importance of incorporating independent study techniques in EFL classrooms to promote learner autonomy and optimize language learning outcomes.